2014
DOI: 10.7314/apjcp.2014.15.22.9603
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of p53 Gene Codon 72 in Endometrial Cancer: Correlation with Tumor Grade and Histological Type

Abstract: Background: Endometrial cancer is the fourth most common cancer among women in developed countries. Patients with endometrial cancer may benefit from systemic chemotherapy alone or in combination with targeted therapies if the disease is clinically diagnosed prior to spread and metastasis to other organs. The aim of this study was to evaluate the prognostic role of p53 polymorphism and its correlation with tumor grade in human uterine endometrial carcinomas. Materials and Methods: A total of 75 patients with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For more effective therapies, a prerequisite may be that the target of choice is commonly involved in GC. The p53 protein has suppressive effects in tumours, and p53 gene alterations are widespread in cancer (7,8,(20)(21)(22). Although mutated forms of p53 are common in GC tissues, their pharmacological significance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For more effective therapies, a prerequisite may be that the target of choice is commonly involved in GC. The p53 protein has suppressive effects in tumours, and p53 gene alterations are widespread in cancer (7,8,(20)(21)(22). Although mutated forms of p53 are common in GC tissues, their pharmacological significance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Regards to other types of endometrial carcinoma, it is worth to note that clear cell and mucinous carcinoma can be found in the EPs also (30). In the minimal endometrial serous carcinoma or EIC, the common genetic mutation which can be confirmed with IHC method is P53 mutation (31). Therefore in the suspicious polyps, IHC staining for P53 will be useful in confirmation of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade the possible association of endometrium cancer with p53 polymorphism codon 72 has been investigated in several human populations. A positive association with the Pro variant has been observed in Korean and other Asiatic populations but not in Caucasian populations [2][3][4][5][6]. In Japanese women a positive association has been found with Arg variant [7].…”
Section: Introductionmentioning
confidence: 92%